Gifts, goods and money : comparing currency and circulation systems in past societies - Brandherm, Dirk,; Heymans, Elon,; Hofmann, Daniela, (Archaeopress Publishing Ltd, 2018)
The papers gathered in this volume explore the economic and social roles of exchange systems in past societies from a variety of different perspectives. Based on a broad range of individual case studies, the authors tackle problems surrounding the identification of (pre-monetary) currencies in the archaeological record.